POLA PENYELESIAN WANPRESTASI PADA KOPERASI SIMPAN PINJAM PEDAGANG INPPRES PASAR RAYA PADANG - Yunimar, Nuraini R dan (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
Regarding the pattern of settlement of defaults in the savings and loan cooperatives of Inpres Pasar Raya Padang traders, the forms of default in this cooperative are delays in payments and also smooth payments. The pattern adopted by cooperatives in solving this is by implementing the Reskedul system, which measures the level of ability of cooperative members in terms of payments. The obstacles faced are basically non-existent because of the awareness of cooperative members to make payments. The small obstacles faced by cooperatives in resolving defaults are due to awareness on the part of cooperative members, giving rise to a sense of belonging that this cooperative is theirs so that cooperatives are important for cooperatives. they. This sense of ownership must be maintained by the management to the members of the cooperative, so that defaults can be avoided as early as possible.